Transformation of blockchain and opportunities for education 4.0 - Ninda Lutfiani; Qurotul Aini; Untung Rahardja; Lidya Wijayanti; Efa Ayu Nabila; Mohammed Iftequar Ali (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
There are many ways in which education 4.0 can continue to develop rapidly and coexist with the development of increasingly advanced technology to bond with each other to be balanced, one of which is using blockchain technology that is integrated in the education sector for various purposes. The main direction in developing global integration in education includes the creating a single educational space and optimization of the interaction between education and stakeholder relationships. The blockchain method implemented in education 4.0 was not widely used because initially, blockchain was only known for the financial sector. Blockchain is comprehensive and appropriate for this era, as blockchain offers technology, trust, and transparency by replacing the previous system with a new system. A particular problem is a need for innovative research to provide new insights into blockchain transformation inf education and application opportunities that can be accepted and used optimally. Researchers used the vast mind method and literature study. The goal is to inform the added value of blockchain that is applied in education as needed, the renewal of research and opportunities for implementing blockchain in education 4.0. The blockchain technology that can be used in education, for example, is archiving, learning, certification and other.